Do Investors Differentiate Return Components? Evidence from Asia Pacific Mutual Funds - Nguyen, Hoang Yen Nhu (2019)
The study aims at investigating determinants of fund performance and factors investors consider when assessing fund managers in Asia Pacific market over the period 2013-2018. Fund alphas are estimated using Single-index model (Jensen, 1968), four-factor model (Carhart, 1997) and seven-factor model (Barber et al., 2016). We find that fund size, fund age and fund’s past performance persistently exhibit explanatory power on fund performance, in which past performance is the key driver. Asia Pacific funds in this period are also documented to exhibit superior performance over the market regardless of estimate models and benchmark choices. By breaking fund returns down into different components, we find that fund alpha remains the dominant factor driving fund flows, revealing the sophistication of investors to account for various return components but only relying on fund performance when determining manager skills and making investment decisions in Asia Pacific market.